2020
DOI: 10.1155/2020/3096826
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Enhancing Effect of a Phytosome Containing the Combined Extract of Mulberry Fruit and Ginger in an Animal Model of Ischemic Stroke with Metabolic Syndrome

Abstract: The prevalence of dementia following cerebral ischemia in metabolic syndrome (MetS) condition is increasing, and most of the cases are often severe. Unfortunately, no effective strategy for treating this condition is available. Based on the positive modulation effect of a polyphenol-rich substance on dementia and the improvement in bioavailability and stability of polyphenols induced by the phytosome technique together with the use of the synergistic concept, we hypothesized that a phytosome containing the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The authors found that PMG reduced acetylcholinesterase, interleukin-6 (IL-6), and malondialdehyde (MDA), but increased glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), catalase (CAT), neuron density, and signal transduction through the extracellular signal-regulated kinase (ERK) pathway. Overall, PMG was found to significantly improve memory [86]. During oxidative stress, the ROS formed in the cells can damage lipids, proteins and nucleic acid.…”
Section: Oxidative Stress and Brain Healthmentioning
confidence: 88%
“…The authors found that PMG reduced acetylcholinesterase, interleukin-6 (IL-6), and malondialdehyde (MDA), but increased glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), catalase (CAT), neuron density, and signal transduction through the extracellular signal-regulated kinase (ERK) pathway. Overall, PMG was found to significantly improve memory [86]. During oxidative stress, the ROS formed in the cells can damage lipids, proteins and nucleic acid.…”
Section: Oxidative Stress and Brain Healthmentioning
confidence: 88%
“…SOD can have a role by scavenging oxygen free radicals in the body ( Zhang L. et al, 2021 ). CAT can disproportionate and decompose oxygen free radicals to produce H 2 O 2 through SOD disproportionation to avoid cytotoxicity ( Wattanathorn et al, 2020 ). MDA is the final product of oxygen-derived free radicals and lipid peroxidation and an important sign of oxidative damage ( Du et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wattanathorn et al [ 80 ] studied the combined effects of mulberry fruit and ginger (PMG) contained in a phytosome in an in vivo experimental model of MetS. To induce MetS, male Wistar rats underwent a high-fat and carb diet for 16 weeks.…”
Section: Effects Of Ginger In Vd Studiesmentioning
confidence: 99%